Geochemistry of a silver-lead-zinc hydrothermal system : ore genesis for the McKay Hill and Horseshoe Hill silver claims in Yukon, Canada - Lara, Hernan Javier (2017)
McKay Hill is located in the Ogilvie Mountains, 50 km north of Keno City, Yukon, Canada. The Wernecke Supergroup was deformed by Late Jurassic and Early Cretaceous arc magmatism and orogeny. Mineral phase identification was performed on 14 ore and 15 gangue samples from McKay Hill and Horseshoe Hill using the x-ray diffractometer MiniFlex 600. Centrifugation was conducted to align clay minerals along the one-dimensional plane from their crystal faces and to disperse the silt and sand grains. XRF analysis was performed on the Rigaku NEX QC X-ray fluorescence analyzer to determine the chalcophile elements and transition elements. Horseshoe is a basalt, consisting of clinopyroxene (25%), orthopyroxene (9%), plagioclase (31%). McKay Hill is a basalt, consisting of clinopyroxene (20%), orthopyroxene (9%), and plagioclase (30%). Ore minerals include argentite and freibergite. The fugacity of oxygen in tholeiitic magmatic series was controlled by the ilmenite series. Dublin Gulch and McKay Hill show consistent orientation due to the presence of the McQuesten Anticlinorium in western Selwyn Basin. Assessing the anomalies in spidergrams, it could be inferred that Eu2+ substitutes for Ca2+ due to its ionic potential. This Cordilleran Ag-Pb-Zn vein deposit is distinguished by the distribution of refractory metals (Ti, Zr, Cr) and pervasive alteration. Thesis (M.S.) Department of Geological Sciences Methods -- Petrographic data -- Aluminosilicate XRD data -- XRF data : introduction -- Discussion.